Effects of a foot strengthening program on foot muscle morphology and running mechanics: A proof-of-concept, single-blind randomized controlled trial. (March 2020) - Taddei, Ulisses T.; Matias, Alessandra B.; Ribeiro, Fernanda I.A.; Bus, Sicco A.; Sacco, Isabel C.N.
Abstract: Objectives: To investigate the effects of a foot training program on muscle morphology and strength as well as running biomechanics in healthy recreational runners. Design: Proof-of-concept, single-blind randomized controlled trial. Settings: Runners were allocated to a control (CG) or an intervention (IG) group. The intervention focused on strengthening the intrinsic foot muscles and their activation during weight-bearing activities. All participants were assessed at baseline and after 8-weeks. Participants: Twenty-eight healthy recreational long-distance runners not habituated to minimalist running shoes or barefoot running. Main outcomes measures: Outcomes were hallux and toes strength; foot function, cross-sectional area and volume of the abductor hallucis (ABH), abductor digiti minimi (ABV), flexor digitorum brevis (FDB), and flexor hallucis brevis; medial longitudinal arch range of motion and stiffness; vertical and antero-posterior propulsive impulses during running. Results: Compared to the CG, an increase was found in the IG for the volume of all muscles investigated and for vertical propulsive impulse during running. Correlations were found between vertical propulsive impulse and volume of ABH(r = 0.40), ABV(r = 0.41), and FDB(r = 0.69). Conclusion: The foot exercise protocol effectively increased intrinsic foot muscle volume and propulsive forces in recreational runners. This shows that intrinsic muscle strengthening affects running mechanics and suggests that it may improve running performance. Highlights: 8-weeks of foot exercises increased the intrinsic foot muscles volumes up to 22.3%. Strengthening the intrinsic foot muscles positively affected running biomechanics. Running vertical propulsive impulses increased after the intervention in runners. Foot arch stiffness and motion did not change after the intervention.